1998
DOI: 10.1037/0096-1523.24.5.1454
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the attentional blink: Visual masking by object substitution.

Abstract: If 2 targets are to be identified among distractors displayed in rapid sequence, correct identification of the 1st target hinders identification of the 2nd. To obtain this additional blink (AB), the 1st target must be masked with a simultaneous (integration) or a delayed (interruption) mask indifferently. In 3 experiments, it was shown that the 2nd target must also be masked, but that the precise form of masking is important: An AB occurs with interruption but not with integration masking. This nonequivalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
351
5
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 210 publications
(401 citation statements)
references
References 35 publications
44
351
5
1
Order By: Relevance
“…The similar findings of both experiments suggest that interference of activity in visual cortex reliably impaired memory consolidation, thereby affecting memory performance. Our findings are in line with previous interference studies that showed a critical window for VSTM consolidation up to 500 ms after stimulus offset (Chun and Potter, 1995;Magnussen et al, 1996;Giesbrecht and Di Lollo, 1998;Jolicoeur and Dell'Acqua, 1998;Lalonde and Chaudhuri, 2002;Vogel et al, 2006), and reveal a neurophysiological correlate of this consolidation window that includes activation states of topographic early visual cortex, which suggests that VSTM representations may be formed or maintained in sensory brain areas that encoded the stimuli. To our knowledge, we are the first to show that topographic early visual cortex is functionally relevant for short-term consolidation of sensory visual information.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The similar findings of both experiments suggest that interference of activity in visual cortex reliably impaired memory consolidation, thereby affecting memory performance. Our findings are in line with previous interference studies that showed a critical window for VSTM consolidation up to 500 ms after stimulus offset (Chun and Potter, 1995;Magnussen et al, 1996;Giesbrecht and Di Lollo, 1998;Jolicoeur and Dell'Acqua, 1998;Lalonde and Chaudhuri, 2002;Vogel et al, 2006), and reveal a neurophysiological correlate of this consolidation window that includes activation states of topographic early visual cortex, which suggests that VSTM representations may be formed or maintained in sensory brain areas that encoded the stimuli. To our knowledge, we are the first to show that topographic early visual cortex is functionally relevant for short-term consolidation of sensory visual information.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, TMS may decrease the strength of or overwrite the neural representation of the memory trace in visual cortex. This suggestion is in line with propositions of object substitution in visual memory after presentation of a competing stimulus (Giesbrecht and Di Lollo, 1998;Enns and Di Lollo, 2000). Furthermore, our finding of a lateralized TMS effect on memory performance suggested that the neural memory representation was retinotopically organized, with limited transfer of memorized information to other parts of the visual field (Karni and Sagi, 1993;Schoups et al, 1995;Dill and Fahle, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been proposed that the mask contributes to the attentional blink because it interferes with (e.g., replaces or prevents the consolidation of) the target information in visual working memory (Brehaut et al, 1999;Giesbrecht & Di Lollo, 1998). If this is the case, then this would be a likely explanation for the effects here, too.…”
Section: Perception Attention or Visual Working Memory?mentioning
confidence: 88%
“…The experimental paradigm we used bears some resemblance to the attentional blink paradigm, in which two visual targets are presented within a continuous flow of nontarget stimuli (Raymond et al, 1992). Studies using such paradigms have shown that, when the time interval between the two target stimuli is short (typically Ͻ500 ms) and when the second target stimulus is quickly masked by a subsequent stimulus, the ability to detect the second target is significantly impaired (Giesbrecht and Di Lollo, 1998). This attentional blink phenomenon is thought to result from the early cortical representation of the second target being overwritten by the subsequent nontarget stimulus, while the central processes required for its consolidation are still engaged by the first target.…”
Section: Methodsmentioning
confidence: 99%